The state and economic enterprise in Japan : essays in the political economy of growth - Lockwood, William W.; Conference on Modern Japan (Princeton, N.J. : Princeton University Press, 1965)
This volume includes contributions to a seminar sponsored by the Conference on Modern Japan and held at Estes Park, Colo., in June 1963.
Includes bibliographical footnotes and index.
lje 28/09/2018
Loans
Keywords: Industrial policy; Japan